Probabilistic seismic hazard assessments for Myanmar and its metropolitan areas - Yang, Huan-Bin (2024)
Although Myanmar is an earthquake-prone country, there has not been proposed an official national seismic hazard map. Thus, this study conducted a probabilistic seismic hazard assessment for Myanmar and some of its metropolitan areas. Performing this assessment required a set of databases that incorporates both earthquake catalogs and fault parameters. We obtained seismic parameters from the International Seismological Centre, and the fault database includes fault parameters from paper reviews and the database. Based on seismic activities, we considered three categories of seismogenic sources—active fault source, shallow area source, and subduction zone source. We evaluated seismic activity of each source based on the earthquake catalogs and fault parameters. Evaluating the ground-shaking behaviors for Myanmar requires evaluation of ground-shaking attenuation; therefore, we validated existing ground motion prediction equations (GMPEs) by comparing instrumental observations and felt intensities for recent earthquakes. We then incorporated the best fitting GMPEs into our seismic hazard assessments. By incorporating the V s30 (the average shear velocity down to 30 m depth) map from an analysis of topographic slope, we utilized site effect and assessed national probabilistic seismic hazards for Myanmar. The assessment shows highest seismic hazard levels near those faults with high slip rates, including the Sagaing Fault and along the Western Coast of Myanmar. We also assessed seismic hazard for some metropolitan cities, including Bagan, Bago, Mandalay, Sagaing, Taungoo and Yangon, in the forms of hazard curves and disaggregation by implementing detailed V s30 maps from micro-tremor surveys. The city-scale assessments show higher hazards for sites close to an active fault or/and with a low V s30, demonstrating the importance of investigating site conditions. The outcomes of this study will be beneficial to urban planning on a city scale and building code legislation on a national scale.